Geomechanics of rock array for chamber system of coal deposits development on the example of finalizing by KGRP complex - Bykadorov Alexey; Degtyarev Dmitry; Smirnov Sergey; Pechenegov Oleg (E3S Web of Conferences, 2017)
The results of systematic instrumental observations of Earth’s surface’s subsidence which was undermined by SHM (Superior Highwall Miners) are given. The regularities of subsidence are revealed. The empirical relationships are established. The methodical provisions for calculating the expected displacements and deformations of the undermined earth’s surface are given.